(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The present article gives a detailed description of the extraction and use of fibers of the majagua tree (Pseudobombax septenatum) for making lines and beach seines in Taganga-Santa Marta. As a result of the demands of a growing number of fishermen, these trees became almost extinct by 1950. Today, all of this fishing gear in Taganga is made with artificial fibers.